Dual targeting with 224Ra/212Pb-conjugates for targeted alpha therapy of disseminated cancers: A conceptual approach - Juzeniene, Asta; Stenberg, Vilde Yuli; Bruland, Øyvind Sverre; Revheim, Mona-Elisabeth; Larsen, Roy Hartvig (Frontiers in Medicine, 2023)
Metastases are the primary cause of death among cancer patients and efficacious new treatments are sorely needed. Targeted alpha-emitting radiopharmaceuticals that are highly cytotoxic may fulfil this critical need. The focus of this paper is to describe and explore a novel technology with potentially broad therapeutic applications that may improve the therapeutic effect of targeted alpha therapy by combining two radionuclides from the same decay chain in the same solution. We hypothesize that the dual alpha targeting solution containing bone-seeking 224Ra and cell-directed complexes of progeny 212Pb is a promising approach to treat metastatic cancers with bone and soft tissue lesions as well as skeletal metastases of mixed lytic/osteoblastic nature. A novel liquid 224Ra/212Pb-generator for rapid preparation of a dual alpha targeting solution is described. Cancer cell targeting monoclonal antibodies, their fragments, synthetic proteins or peptides can all be radiolabelled with 212Pb in the 224Ra-solution in transient equilibrium with daughter nuclides. Thus, 224Ra targets stromal elements in sclerotic bone metastases and 212Pb-chelated-conjugate targets tumor cells of metastatic bone cancer or osteosarcoma. The dual alpha solution may also be explored to treat metastatic breast cancer or multiple myeloma after manipulation of bone metastases to a more osteoblastic phenotype by the use of bisphosphonates, denosumab, bortezomib or hormone therapy prior to treatment. This may improve targeting of bone-seeking 224Ra and render an augmented radiation dose deposited within metastases. Our preliminary preclinical studies provide conceptual evidence that the dual alpha 224Ra-solution with bone or tumor-targeted delivery of 212Pb has potential to inhibit cancer metastases without significant toxicity. In some settings, the use of a booster dose of purified 212Pb-conjugate alone could be required to elevate the effect of this tumor cell directed component, if needed, e.g. in a fractionated treatment regimen, where the dual targeting solution will act as maintenance treatment.